Pengelolaan Konten Instagram Humas Jabar Sebagai Media Informasi Masyarakat di Jawa Barat - Vina Salsabila Firmana; Privo Subekti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
. Anies Rasyid Baswedan is a politician with an academic background. He joined two other contenders as a candidate in The Presidential Election of 2024, which required him to participate in The 2024 Presidential Candidate Debate. Compared to the other candidates, Anies was thought to have had strong performance and rhetorical abilities, particularly in discussions pertaining to education. Thus, the purpose of this study is to evaluate the rhetoric used by Anies Baswedan to bring up the subject of education in Indonesia during the 2024 presidential debate. This research uses a constructivist paradigm and descriptive qualitative research methods. Three types of rhetorical evidence are examined in this study using an Aristotelian rhetorical approach: ethos, pathos, and logos. In this study, seven units of analysis were examined. Eight ethos forms, four pathos forms, and eight logos forms were identified by the researchers from the seven units of study. The analysis's findings demonstrate Anies Baswedan's proficiency and effectiveness with rhetoric in influencing listeners during political campaigns. Keywords: , , , , .